Why EC environmental policy will affect American business. - VIAL, Catherine (1993)
Presents a brief overview of EC environmental policy. Notes that harmonization of member states' environmental legislation has been successful in several areas, e.g. air and noise emissions for motor vehicles, and the disposal of dangerous substances and waste into water. Places emphasis on packaging, the recovery of packaging waste, and the need for a 'green' corporate image for manufacturers. Points out that US industry has developed valuable experience in this area, and this expertise can now be marketed to their advantage in Europe.